Collagen molecule-graphene oxide compound, preparation method thereof and application of collagen molecule-graphene oxide compound in cement-based material

Through the composite coating technology of collagen molecules and graphene oxide, the problem of uneven dispersion of graphene oxide in cement-based materials is solved, and the ultra-low doping and uniform dispersion of graphene oxide is achieved, which significantly improves the strength of concrete and durability and reduce costs.

CN119306418APending Publication Date: 2025-01-14SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477691.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Graphene oxide is difficult to disperse evenly in cement-based materials, resulting in large amounts of doping, high cost and unstable application performance.

Method used

Collagen molecules and graphene oxide form a composite. By degrading waste dandruff into collagen molecules and combining with graphene oxide, the amino group, carboxyl group, hydroxyl group and hydrogen bond in the double helix structure form spherical agglomerates and coat graphene oxide. The ene nanosheet layer achieves uniform dispersion in the cement-based material.

Benefits of technology

Ultra-low doping and uniform dispersion of graphene oxide are achieved, which significantly improves the strength and durability of concrete and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306418A_ABST
    Figure CN119306418A_ABST
Patent Text Reader

Abstract

The invention discloses a collagen molecule-graphene oxide compound, a preparation method thereof and application of the collagen molecule-graphene oxide compound in a cement-based material, and belongs to the technical field of preparation of graphene oxide nanomaterials. Waste leather scraps are degraded into collagen molecules, and the collagen molecule-graphene oxide compound is formed by the collagen molecules and graphene oxide. The graphene oxide is doped into a cement-based material, so that the graphene oxide is uniformly dispersed in the cement-based material. Collagen molecules exist in a solution in a state of intertwined aggregates, and can generate intermolecular acting force, hydrogen bonds and the like with groups on a graphene oxide sheet layer when in a graphene oxide environment, so that the collagen molecule aggregates surround the graphene oxide nanosheet layer to form a coated collagen molecule-graphene oxide compound; the graphene oxide is uniformly dispersed in a small-size nano-scale manner, so that ultra-low doping amount and uniform dispersion of the graphene oxide can be realized by doping the graphene oxide into a cement-based material, and the strength and durability of concrete are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphene oxide nanomaterial preparation, and specifically relates to a collagen molecule@graphene oxide composite and a preparation method thereof and application thereof in cement-based materials. Background Art

[0002] Graphene oxide nanosheets have been used in cement-based materials for more than ten years. The key problem that currently plagues the application and function of graphene oxide (GO) in cement-based materials is that it is difficult to disperse evenly in the cement matrix. At present, many research works have been carried out around this issue. The methods to improve the dispersion effect of GO mainly include physical dispersion and chemical dispersion. The physical dispersion method mainly includes ultrasonic dispersion, polymer dispersant or inorganic micro-nanoparticle dispersion. For example, GO is dispersed by ultrasonic pretreatment and polycarboxylate water reducer (PC), metakaolin (MK) and PC are used to form a composite material with GO for dispersion, and nano-silica (NS) is added to the GO dispersion to improve the dispersion of GO in cement. The results show that the use of ultrasound and PC, MO, NS, etc. can improve the dispersion of GO, but it cannot form a single layer or a few layers of uniform dispersion. The chemical modification method is to modify the chemical groups on the GO nanosheet to improve the dispersion effect of GO nanosheets in cement paste. For example, hydroxyl groups were introduced into GO nanosheets and then water-soluble hydroxylated graphene (HO-GO) was prepared by simple ball milling. HO-GO has good hydrophilicity and dispersibility compared with GO. The effect of KH550 grafting modification of GO (MGO) on cement-based composites showed that organic siloxane groups were grafted on the surface of MGO, which reduced the interaction between GO sheets and improved the dispersibility of MGO in cement paste. GO (CFGOs) was chemically grafted with three polymers with different polyetheramine branch lengths. The increase in branch length consumed a large amount of carboxyl groups (-COOH) at the edge of GO nanosheets. The steric hindrance effect of the branch weakened the intermolecular interaction between CFGOs sheets, allowing GFGOs to be evenly dispersed in a single sheet in cement-based materials. The problem with the chemical modification method is that the chemical modification process is complicated and cumbersome, resulting in increased costs. The result of chemical modification reduces the chemical groups on the GO nanosheets, reduces the interaction between GO sheets, and also reduces the ability of GO nanosheets to regulate the morphology of cement hydration products.

[0003] At present, the research results at home and abroad show that the problem of uniform dispersion of GO in cement-based materials has not been solved, resulting in large GO dosage, high cost and unstable application performance, which restricts the application of GO in cement-based materials. At present, the research results at home and abroad show that the dosage of GO is in the range of 0.03%~0.1%, which is a large dosage for GO and generates high cost.

[0004] In view of the technical problems that the existing graphene oxide is unevenly doped in cement-based materials, resulting in large graphene oxide dosage, high cost and unstable application performance in cement-based materials, it is urgent to find a new graphene oxide composite to achieve ultra-low dosage and uniform dispersion of graphene oxide in cement-based materials, improve the strength and durability of concrete, and reduce costs. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a collagen molecule @ graphene oxide composite and a preparation method thereof and application in cement-based materials, so as to solve the technical problems that the existing graphene oxide is unevenly doped in cement-based materials, resulting in a large amount of graphene oxide in the cement-based materials, high cost and unstable application performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a collagen molecule@graphene oxide composite, comprising the following steps: 1) Mixing the waste skin scraps with the alkaline solution, adding the first portion of the amphoteric surfactant, stirring and reacting for the first time, and filtering to obtain a collagen fiber solution; adjusting the pH value to 9.0-10.0 with citric acid, adding alkaline protease, and stirring and reacting for the second time to obtain a collagen molecule solution; adjusting the pH value to 7.0-8.0 with citric acid, adding the second portion of the amphoteric surfactant and pentaerythritol, and stirring to obtain a collagen molecule spherical aggregate dispersion; 2) adding graphene oxide to a pentaerythritol solution, and subjecting it to ultrasonic treatment to obtain a graphene oxide dispersion, and then adding the collagen molecule spherical aggregate dispersion prepared in step 1), stirring, and allowing it to stand to obtain a collagen molecule@graphene oxide complex.

[0007] Preferably, in step 1), the mass ratio of waste skin scraps, alkaline solution and the first amphoteric surfactant is (50-60): (200-250): (2-3); the mass ratio of collagen fiber solution, alkaline protease, the second amphoteric surfactant and pentaerythritol is (200-250): (5-8): (2-3): (0.1-0.3).

[0008] Preferably, in step 1), the conditions for the first stirring reaction are: stirring at 50-60° C. for 13-15 h; the conditions for the second stirring reaction are: stirring at 50-60° C. for 6-8 h; and the stirring time is 30-40 min.

[0009] Preferably, in step 1), the waste leather scraps are discarded cowhides, sheepskins or pigskins produced in the trimming or shaving process of the tannery before tanning; the waste leather scraps have a size range of 1 to 3 mm, a moisture content of less than 12%, an ash content of 5% to 7%, a protein content of more than 75%, and a content of other impurities of 2.0% to 2.5%.

[0010] Preferably, in step 1), the alkaline solution is prepared by dissolving at least one of sodium hydroxide and potassium hydroxide in deionized water, and the mass fraction of the alkaline solution is 2% to 5%.

[0011] Preferably, in step 1), the enzymatic activity of the alkaline protease is in the range of 200,000 to 500,000 u / g, the pH value is 9 to 11, and the applicable temperature is 50 to 60°C; the first amphoteric surfactant and the second amphoteric surfactant are one or a mixture of sodium N-dodecyl-aminopropionic acid, dodecyl imidazoline betaine, N-dodecyl-N,N-dimethyl-N-carboxymethyl betaine and N,N-2-methyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt, the active matter mass percentage is 30%, and the pH value is 6.0 to 8.0.

[0012] Preferably, in step 1), the oxygen content of graphene oxide is 26.85 at%, and the particle size is 50-350 nm.

[0013] Preferably, in step 1), the pentaerythritol solution is prepared by mixing deionized water and pentaerythritol; the mass ratio of graphene oxide, deionized water, pentaerythritol and collagen molecular spherical aggregate dispersion is (50-60): (80-100): (1-1.5): (200-250); and the stirring time is 20-30 min.

[0014] The invention also discloses a collagen molecule@graphene oxide composite, which is prepared by the above preparation method.

[0015] The present invention also discloses the use of the collagen molecule@graphene oxide complex prepared by the preparation method in the preparation of cement-based materials, wherein 20 to 30 parts of the collagen molecule@graphene oxide complex are added to every 100 parts of the cement-based materials.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a collagen molecule @ graphene oxide composite. The intermolecular forces, hydrogen bonds and electrostatic forces between the amino groups, carboxyl groups and hydroxyl groups in the double helix structure of the collagen molecule not only make the collagen molecule form agglomerates in the form of mutually entangled spherical agglomerates, but also the agglomerated collagen molecules can generate intermolecular forces, hydrogen bonds and the like with the groups on the graphene oxide sheets when they are in the graphene oxide environment, resulting in the collagen molecule agglomerates forming a coating type composite with good stability around the graphene oxide nanosheets, blocking the agglomeration of graphene oxide, and graphene oxide presenting small-sized nano-scale uniform dispersion in the collagen molecule @ graphene oxide. At the same time, the cost of the prepared cement-based material is also significantly reduced. Compared with conventional physical methods, the method has a more stable and uniform dispersion effect, and compared with conventional chemical dispersion methods, the method has the advantages of not destroying the graphene oxide structure and chemical groups and improving the dispersion effect. The preparation process is relatively simple and low-cost, and it achieves uniform dispersion of graphene oxide nanosheets in cement-based materials, achieves ultra-low dosage and significantly improves the strength, crack resistance and permeability resistance of cement-based materials.

[0017] The invention discloses a collagen molecule @ graphene oxide composite obtained by the above-mentioned preparation method. According to the existence state and dispersion behavior of graphene oxide, a collagen molecule @ graphene oxide composite with a small molecular weight is prepared. The collagen molecule with a small molecular weight exists in the form of mutually entangled spherical aggregates in the solution. When the aggregated collagen molecule is in the graphene oxide environment, it can generate intermolecular forces, hydrogen bonds, etc. with the groups on the graphene oxide sheet layer, resulting in the collagen molecule aggregates surrounding the graphene oxide nanosheet layer to form a coated composite, blocking the agglomeration of graphene oxide. In the collagen molecule @ graphene oxide composite, the graphene oxide presents a small-size nano-scale uniform dispersion, and the graphene oxide is added to the cement-based material to achieve ultra-low addition and uniform dispersion of graphene oxide. The collagen molecule with a small molecular weight is itself a surfactant, which has the functions of dispersion and air entrainment. The addition of collagen molecule @ graphene oxide not only promotes the uniform dispersion of the graphene oxide nanosheet layer, but also has the function of improving the dispersion uniformity and stability of the cement-based material system.

[0018] The present invention also discloses the use of the collagen molecule@graphene oxide composite obtained by the above preparation method in the preparation of cement-based materials. Adding the collagen molecule@graphene oxide composite into cement-based materials can achieve ultra-low addition (less than 0.001%) and uniform dispersion of graphene oxide, thereby significantly improving the strength and durability of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the process of degradation of waste leather into collagen molecules disclosed in the present invention; Figure 2 It is a schematic diagram of the structure of the collagen molecule@graphene oxide complex disclosed in the present invention. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0021] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0022] The present invention is further described in detail below in conjunction with the accompanying drawings: The present invention discloses a method for preparing a collagen molecule@graphene oxide composite, comprising the following steps: (1) Method for preparing collagen spherical aggregate dispersion by degrading waste dandruff Step 1, 50-60 parts of waste skin scraps are mixed with 200-250 parts of alkaline solution, 2-3 parts of amphoteric surfactant are added, and the mixture is stirred at 50-60° C. for 13-15 hours, and the degradation solution is filtered to remove the residue, and the filtrate is a collagen fiber solution; Step 2: 200-250 parts of the collagen fiber solution prepared in step 1 are adjusted to a pH of 9.0-10.0 with citric acid, 5-8 parts of alkaline protease are added, and the mixture is stirred at 50-60° C. for 6-8 hours to obtain a collagen molecule solution.

[0023] Step 3: The collagen molecule solution prepared in step 2 is adjusted to pH 7.0-8.0 with citric acid, 2-3 parts of amphoteric surfactant and 0.1-0.3 parts of pentaerythritol are added, and stirred for 30-40 minutes to obtain a dispersion of spherical aggregates of collagen molecules.

[0024] (2) Preparation method of collagen molecule@graphene oxide composite 50-60 parts of graphene oxide are added to a solution formed by 80-100 parts of water and 1-1.5 parts of pentaerythritol, and ultrasonic treatment is performed for 30 minutes to uniformly disperse the graphene oxide to obtain a graphene oxide dispersion. 200-250 parts of the collagen molecule spherical aggregate dispersion prepared in step 3 are added thereto, stirred for 20-30 minutes, and allowed to stand for 60 minutes to obtain a collagen molecule@graphene oxide complex.

[0025] Furthermore, waste leather shavings are waste leather shavings generated by tanneries during trimming and shaving processes before tanning, including waste leather shavings from various animal skins such as cowhide, sheepskin, and pigskin. Since waste leather shavings vary in size, they need to be crushed before use to make their size range 1~3mm, the moisture content less than 8%~12%, the ash content 5%~7%, the protein content greater than 75%~80%, and the content of other impurities 2.0%~2.5%.

[0026] Furthermore, the alkaline solution is prepared by dissolving sodium hydroxide, potassium hydroxide or a mixture thereof in deionized water, with a mass fraction of 2% to 5%.

[0027] Furthermore, the enzymatic activity range of the alkaline protease is 200,000 to 500,000 u / g, the suitable pH value is 9 to 11, and the suitable temperature is 50 to 60°C.

[0028] Furthermore, the amphoteric surfactant is one or a mixture of N-dodecyl-aminopropionic acid sodium, dodecyl imidazoline betaine amphoteric surfactant, N-dodecyl-N,N-dimethyl-N-carboxymethyl betaine and N,N-2-methyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt, with an active matter mass percentage of 30% and a pH value of 6.0~8.0.

[0029] Furthermore, a graphene oxide dispersion is prepared by a Hummer method, the oxygen content of the graphene oxide is 26.85 at%, the particle size is 50-350 nm, and the mass fraction of the graphene oxide in the graphene oxide dispersion is 0.1%-1.2%.

[0030] The collagen molecule @ graphene oxide composite prepared by the above-mentioned preparation method disclosed in the present invention, the intermolecular force, hydrogen bond and electrostatic force between the amino group, carboxyl group and hydroxyl group in the double helix structure of the collagen molecule not only make the collagen molecule form an aggregate in the form of mutually entangled spherical aggregates, but also the aggregated collagen molecule can produce intermolecular force, hydrogen bond and the like with the groups on the graphene oxide sheet when in the graphene oxide environment, resulting in the collagen molecule aggregates surrounding the graphene oxide nanosheet to form a coating type composite with good stability, blocking the agglomeration of graphene oxide, and the graphene oxide in the collagen molecule @ graphene oxide presents small-sized nano-scale uniform dispersion. The graphene oxide nanosheet is uniformly dispersed in the cement-based material, achieving ultra-low dosage and significantly improving the strength, crack resistance and penetration resistance of the cement-based material. The collagen molecule itself is a surfactant with the function of dispersion and air entrainment. The addition of collagen molecule @ graphene oxide not only promotes the uniform dispersion of the graphene oxide nanosheet, but also has the function of improving the dispersion uniformity and stability of the cement-based material system.

[0031] The application of the collagen molecule@graphene oxide composite disclosed in the present invention in preparing cement-based materials comprises the following steps: The amount of the collagen molecule @ graphene oxide complex solution added is calculated according to the weight of cement in the cement-based composite. The amount of the collagen molecule @ graphene oxide complex solution added is 20 to 30 parts per 100 parts of cement. Before adding, the collagen molecule @ graphene oxide complex dispersion is evenly mixed with mixing water. The weight of the added collagen molecule @ graphene oxide complex solution is calculated in the mixing water. The cement-based composite material mixed with the collagen molecule @ graphene oxide complex is prepared according to conventional preparation methods of cement-based composite materials such as mortar and concrete.

[0032] When the collagen molecule@graphene oxide composite prepared by the present invention is added into cement-based materials during the preparation of cement-based materials, ultra-low addition amount (less than 0.001%) of graphene oxide and uniform dispersion can be achieved, thereby significantly improving the strength and durability of concrete.

[0033] See also Figure 1 The present invention is a schematic diagram of the process of degradation of waste leather into collagen molecules; as can be seen from the figure, the collagen molecules formed after dandruff is degraded by alkali and enzymes always exist in the solution as agglomerates formed by curling and winding, which is the result of the double helix structure in the collagen molecules and the strong hydrogen bonds and intermolecular forces between the collagen molecules.

[0034] Figure 2This is a schematic diagram of the structure of the collagen molecule @ graphene oxide complex disclosed in the present invention; as can be seen from the figure, when the aggregated collagen molecules are in a graphene oxide environment, they can generate intermolecular forces, hydrogen bonds, etc. with the groups on the graphene oxide sheets, resulting in the collagen molecule aggregates forming a very stable coated complex around the graphene oxide nanosheets, blocking the agglomeration of graphene oxide, and the graphene oxide in the collagen molecule @ graphene oxide is uniformly dispersed at the small nanoscale.

[0035] Example 1 A method for preparing a collagen molecule@graphene oxide composite comprises the following steps: Step 1. Mix 50 parts of waste cowhide shavings with a size of 1 mm, a moisture content of 12%, an ash content of 5%, a protein content of 80%, and a content of other impurities of 2% with 200 parts of a 2% sodium hydroxide solution by mass, add 2 parts of an amphoteric surfactant N-dodecyl-aminopropionic acid sodium with a mass percentage of 30% and a pH value of 6.0, stir and react at 50°C for 13 hours, filter the degradation solution to remove the residue, and the filtrate is a collagen fiber solution.

[0036] Step 2: Adjust 200 parts of the collagen fiber solution prepared in step 1 to a pH of 9.0 with citric acid, add 5 parts of alkaline protease with an enzyme activity of 200,000 u / g, a suitable pH of 9, and a suitable temperature of 50°C, stir at 50°C for 6 hours to obtain a collagen molecule solution.

[0037] Step 3: The collagen molecule solution prepared in step 2 is adjusted to pH 7.0 with citric acid, 2 parts of amphoteric surfactant sodium N-dodecyl-aminopropionate and 0.1 parts of pentaerythritol are added, and stirred for 30 minutes to obtain a dispersion of spherical aggregates of collagen molecules.

[0038] Step 4: Add 50 parts of graphene oxide with an oxygen content of 26.85 at% and a particle size of 50 nm to a solution formed by 80 parts of water and 1 part of pentaerythritol, and ultrasonically treat for 30 minutes to uniformly disperse the graphene oxide. Add 200 parts of the collagen spherical aggregate dispersion prepared in step 3, stir for 20 minutes, and stand for 60 minutes to obtain a collagen molecule@graphene oxide complex.

[0039] The amount of the collagen molecule @ graphene oxide composite solution added is calculated according to the weight of cement in the cement-based composite. The amount of the collagen molecule @ graphene oxide composite solution added is 20 parts per 100 parts of cement. Before adding, the collagen molecule @ graphene oxide composite dispersion is evenly mixed with mixing water. The weight of the added collagen molecule @ graphene oxide composite solution is calculated in the mixing water. The cement-based composite material mixed with the collagen molecule @ graphene oxide composite is prepared according to the conventional method for preparing cement-based composite mortar.

[0040] Example 2 A method for preparing a collagen molecule@graphene oxide composite comprises the following steps: Step 1. Mix 60 parts of waste sheepskin shavings with a size of 3 mm, a moisture content of 8%, an ash content of 7%, a protein content of 82.5%, and other impurities with 250 parts of a 2.5% potassium hydroxide solution by mass, add 3 parts of an amphoteric surfactant dodecyl imidazoline betaine with a mass percentage of 30% active matter and a pH value of 8.0, stir and react at 60°C for 15 hours, filter the degradation solution to remove the residue, and the filtrate is a collagen fiber solution.

[0041] Step 2: Adjust 250 parts of the collagen fiber solution prepared in step 1 to a pH of 10.0 with citric acid, add 8 parts of alkaline protease with an enzyme activity of 500,000 u / g, a suitable pH of 11, and a suitable temperature of 60°C, stir at 60°C for 8 hours to obtain a collagen molecule solution.

[0042] Step 3: The collagen molecule solution prepared in step 2 is adjusted to pH 8.0 with citric acid, 3 parts of amphoteric surfactant dodecyl imidazoline betaine and 0.3 parts of pentaerythritol are added, and stirred for 40 minutes to obtain a dispersion of spherical aggregates of collagen molecules.

[0043] Step 4: Add 60 parts of graphene oxide with an oxygen content of 26.85 at% and a particle size of 350 nm to a solution formed by 100 parts of water and 1.5 parts of pentaerythritol, and ultrasonically treat for 30 minutes to uniformly disperse the graphene oxide. Add 250 parts of the collagen spherical aggregate dispersion prepared in step 3, stir for 30 minutes, and stand for 60 minutes to obtain a collagen molecule@graphene oxide complex.

[0044] The amount of the collagen molecule @ graphene oxide complex solution added is calculated according to the weight of cement in the cement-based composite. The amount of the collagen molecule @ graphene oxide complex solution added is 30 parts per 100 parts of cement. Before adding, the collagen molecule @ graphene oxide complex dispersion is evenly mixed with mixing water. The weight of the added collagen molecule @ graphene oxide complex solution is calculated in the mixing water. The cement-based composite material mixed with the collagen molecule @ graphene oxide complex is prepared according to the conventional preparation method of cement-based composite concrete.

[0045] Example 3 A method for preparing a collagen molecule@graphene oxide composite comprises the following steps: Step 1, 53 parts of pig skin waste shavings with a size of 1.5 mm, a moisture content of 10%, an ash content of 6%, a protein content of 81.8%, and a content of other impurities of 2.2% are mixed with 220 parts of a 3% sodium hydroxide solution by mass, and 2.3 parts of an amphoteric surfactant N-dodecyl-N,N-dimethyl-N-carboxymethyl betaine with a mass percentage of 30% of active matter and a pH value of 6.0 are added, and the reaction is stirred at 55° C. for 14 hours, and the degradation solution is filtered to remove the residue, and the filtrate is a collagen fiber solution.

[0046] Step 2: Adjust 220 parts of the collagen fiber solution prepared in step 1 to a pH of 9.3 with citric acid, add 6 parts of alkaline protease with an enzyme activity of 250,000 u / g, a suitable pH of 9.5, and a suitable temperature of 55°C, stir at 53°C for 6.5 hours to obtain a collagen molecular solution.

[0047] Step 3: The collagen molecule solution prepared in step 2 is adjusted to pH 7.5 with citric acid, 2.5 parts of amphoteric surfactant N-dodecyl-N,N-dimethyl-N-carboxymethyl betaine and 0.2 parts of pentaerythritol are added, and stirred for 35 minutes to obtain a dispersion of spherical aggregates of collagen molecules.

[0048] Step 4: Add 55 parts of graphene oxide with an oxygen content of 26.85 at% and a particle size of 150 nm to a solution formed by 90 parts of water and 1.2 parts of pentaerythritol, and ultrasonically treat for 30 minutes to uniformly disperse the graphene oxide. Add 220 parts of the collagen spherical aggregate dispersion prepared in step 3, stir for 25 minutes, and stand for 60 minutes to obtain a collagen molecule@graphene oxide complex.

[0049] The amount of the collagen molecule @ graphene oxide composite solution added is calculated according to the weight of cement in the cement-based composite. The amount of the collagen molecule @ graphene oxide composite solution added is 25 parts per 100 parts of cement. Before adding, the collagen molecule @ graphene oxide composite dispersion is evenly mixed with mixing water. The weight of the added collagen molecule @ graphene oxide composite solution is calculated in the mixing water. The cement-based composite material mixed with the collagen molecule @ graphene oxide composite is prepared according to the conventional method for preparing cement-based composite mortar.

[0050] Example 4 A method for preparing a collagen molecule@graphene oxide composite comprises the following steps: Step 1. Mix 56 parts of pig skin waste shavings with a size of 2 mm, a moisture content of 6%, an ash content of 5.5%, a protein content of 86.2%, and a content of other impurities of 2.3% with 240 parts of a 4% sodium hydroxide and potassium hydroxide alkaline solution, add 2.5 parts of an amphoteric surfactant N, N-2-methyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt with a mass percentage of 30% and a pH value of 6.0, stir and react at 55°C for 14 hours, filter the degradation solution to remove the residue, and the filtrate is a collagen fiber solution.

[0051] Step 2: Adjust 230 parts of the collagen fiber solution prepared in step 1 to a pH of 9.5 with citric acid, add 7 parts of alkaline protease with an enzyme activity of 300,000 u / g, a suitable pH of 9, and a suitable temperature of 58°C, stir at 55°C for 7 hours to obtain a collagen molecule solution.

[0052] Step 3: The collagen molecule solution prepared in step 2 is adjusted to pH 8.0 with citric acid, 2.6 parts of amphoteric surfactant N,N-2-methyl (methacryloyloxyethyl) aminopropanesulfonic acid salt and 0.25 parts of pentaerythritol are added, and stirred for 38 minutes to obtain a dispersion of spherical aggregates of collagen molecules.

[0053] Step 4: Add 55 parts of graphene oxide with an oxygen content of 26.85 at% and a particle size of 550 nm to a solution formed by 90 parts of water and 1.3 parts of pentaerythritol, and ultrasonically treat for 30 minutes to uniformly disperse the graphene oxide. Add 240 parts of the collagen spherical aggregate dispersion prepared in step 3, stir for 28 minutes, and stand for 60 minutes to obtain a collagen molecule@graphene oxide complex.

[0054] The amount of the collagen molecule @ graphene oxide complex solution added is calculated according to the weight of cement in the cement-based composite. The amount of the collagen molecule @ graphene oxide complex solution added is 25 parts per 100 parts of cement. Before adding, the collagen molecule @ graphene oxide complex dispersion is evenly mixed with mixing water. The weight of the added collagen molecule @ graphene oxide complex solution is calculated in the mixing water. The cement-based composite material mixed with the collagen molecule @ graphene oxide complex is prepared according to the conventional preparation method of cement-based composite concrete.

[0055] Example 5 A method for preparing a collagen molecule@graphene oxide composite comprises the following steps: Step 1, 58 parts of pig skin waste shavings with a size of 3 mm, a moisture content of 12%, an ash content of 7%, a protein content of 78.6%, and a content of other impurities of 2.4% are mixed with 240 parts of a 5% sodium hydroxide solution by mass, and 2.6 parts of amphoteric surfactants N-dodecyl-aminopropionic acid sodium and dodecyl imidazoline betaine with a mass percentage of 30% active matter and a pH value of 6.0 are added, and the reaction is stirred at 58°C for 14.5 hours, and the degradation solution is filtered to remove the residue, and the filtrate is a collagen fiber solution.

[0056] Step 2: Adjust 240 parts of the collagen fiber solution prepared in step 1 to a pH of 9.5 with citric acid, add 7 parts of alkaline protease with an enzyme activity of 350,000 u / g, an appropriate pH of 10, and an appropriate temperature of 56°C, stir at 55°C for 7 hours to obtain a collagen molecule solution.

[0057] Step 3: The collagen molecule solution prepared in step 2 is adjusted to pH 7.0 with citric acid, and 2.8 parts of amphoteric surfactant N-dodecyl-N,N-dimethyl-N-carboxymethyl betaine and N,N-2-methyl (methacryloyloxyethyl) aminopropanesulfonic acid salt and 0.20 parts of pentaerythritol are added, and stirred for 35 minutes to obtain a dispersion of spherical aggregates of collagen molecules.

[0058] Step 4: Add 58 parts of graphene oxide with an oxygen content of 26.85 at% and a particle size of 300 nm to a solution formed by 95 parts of water and 1.3 parts of pentaerythritol, and ultrasonically treat for 30 minutes to uniformly disperse the graphene oxide. Add 240 parts of the collagen spherical aggregate dispersion prepared in step 3, stir for 28 minutes, and stand for 60 minutes to obtain a collagen molecule@graphene oxide composite.

[0059] The amount of the collagen molecule @ graphene oxide complex solution added is calculated according to the weight of cement in the cement-based composite. The amount of the collagen molecule @ graphene oxide complex solution added is 30 parts per 100 parts of cement. Before adding, the collagen molecule @ graphene oxide complex dispersion is evenly mixed with mixing water. The weight of the added collagen molecule @ graphene oxide complex solution is calculated in the mixing water. The cement-based composite material mixed with the collagen molecule @ graphene oxide complex is prepared according to the conventional method for preparing cement-based composite mortar.

[0060] Comparative Example The graphene oxide used was mixed with a polycarboxylate water reducer or an amphoteric surfactant, dodecyl dimethyl betaine, and then ultrasonically dispersed for 20 to 30 minutes. The graphene oxide was added to a cement-based composite material at a concentration of 0.002% by weight of cement as a control sample, and its mechanics and durability were tested.

[0061] Table 1 Performance of the samples in the examples

[0062] From the results in the table, it can be seen that the cement-based material sample prepared by the method of the present invention has good slump retention, which shows that the cement-based material prepared by the method of the present invention has good working performance; its compressive strength and flexural strength are significantly improved, which shows that the cement-based material prepared by the method of the present invention has good toughness; its water seepage height, chloride ion permeability, freeze-thaw resistance, carbonization resistance, volume stability, etc. are almost unaffected, which shows that the cement-based material prepared by the present invention has good durability. Therefore, the cement-based material prepared by the method of the present invention has good working performance, volume stability and durability.

[0063] Testing method: Slump is tested according to GB / T50080-2002 "Test Standard for Performance of Ordinary Concrete Mixtures". Compressive strength and flexural strength are tested according to GB50107-2010 "Concrete Strength Test and Evaluation Standard". Water permeability is tested according to GB / T50082-2009, sample size is φ150mm×150mm, penetration pressure is 3.5MPa, and pressurization time is 48h. Freeze-thaw resistance is tested according to JTG E30-2005 "Test Procedure for Cement and Cement Concrete for Highway Engineering". A quick freezing tester is used to measure the frost resistance of concrete. A freeze-thaw cycle lasts 2~5h, the freeze-thaw temperature is -18℃, and the sample size is 100mm×100mm×500mm. Chloride ion permeability is tested according to GB / T50082-2009 to measure the chloride ion diffusion charge and evaluate the chloride ion penetration capacity. The sample size is 100mm×100mm×100mm. The carbonization specimens were tested according to GB / T50082-2009 method “Standard for test methods for long-term performance and durability of ordinary concrete”, and the specimen size was 100mm×100mm×100mm.

[0064] The present invention discloses a collagen molecule @ graphene oxide composite material and a preparation method thereof and an application thereof in cement-based materials. Aiming at the problem that graphene oxide is difficult to be uniformly dispersed in a cement matrix, waste leather is degraded into small molecular weight collagen molecules and the composite material is formed with graphene oxide into a collagen molecule @ graphene oxide composite material, which is then added into the cement-based material to achieve uniform dispersion of graphene oxide therein. Small molecular weight collagen molecules exist in the form of mutually entangled spherical aggregates in a solution. When such aggregated collagen molecules are in a graphene oxide environment, they can generate intermolecular forces, hydrogen bonds, etc. with groups on graphene oxide sheets, resulting in the formation of a coated composite material of collagen molecule aggregates around graphene oxide nanosheets, blocking the agglomeration of graphene oxide. In the collagen molecule @ graphene oxide, graphene oxide is uniformly dispersed at a small nanometer level. Adding the composite material into cement-based materials can achieve ultra-low addition and uniform dispersion of graphene oxide, significantly improving the strength and durability of concrete.

[0065] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a collagen molecule@graphene oxide composite, characterized in that: The steps include: 1) Mixing the waste skin scraps with the alkaline solution, adding the first portion of the amphoteric surfactant, stirring and reacting for the first time, and filtering to obtain a collagen fiber solution; adjusting the pH value to 9.0-10.0 with citric acid, adding alkaline protease, and stirring and reacting for the second time to obtain a collagen molecule solution; adjusting the pH value to 7.0-8.0 with citric acid, adding the second portion of the amphoteric surfactant and pentaerythritol, and stirring to obtain a collagen molecule spherical aggregate dispersion; 2) adding graphene oxide to a pentaerythritol solution, and subjecting it to ultrasonic treatment to obtain a graphene oxide dispersion, and then adding the collagen molecule spherical aggregate dispersion prepared in step 1), stirring, and allowing it to stand to obtain a collagen molecule@graphene oxide complex.

2. The method for preparing the collagen molecule@graphene oxide composite according to claim 1, characterized in that: In step 1), the mass ratio of the waste skin scraps, the alkaline solution and the first amphoteric surfactant is (50-60): (200-250): (2-3); the mass ratio of the collagen fiber solution, alkaline protease, the second amphoteric surfactant and pentaerythritol is (200-250): (5-8): (2-3): (0.1-0.3).

3. The method for preparing the collagen molecule@graphene oxide composite according to claim 1, characterized in that: In step 1), the conditions for the first stirring reaction are: stirring at 50-60° C. for 13-15 hours; the conditions for the second stirring reaction are: stirring at 50-60° C. for 6-8 hours; and the stirring time is 30-40 minutes.

4. The method for preparing the collagen molecule@graphene oxide composite according to claim 1, characterized in that: In step 1), the waste leather scraps are discarded cowhide, sheepskin or pigskin produced in the trimming or shaving process of the tannery before tanning; the waste leather scraps have a size range of 1 to 3 mm, a moisture content of less than 12%, an ash content of 5% to 7%, a protein content of more than 75%, and a content of other impurities of 2.0% to 2.5%.

5. The method for preparing the collagen molecule@graphene oxide composite according to claim 1, characterized in that: In step 1), the alkaline solution is prepared by dissolving at least one of sodium hydroxide and potassium hydroxide in deionized water, and the mass fraction of the alkaline solution is 2% to 5%.

6. The method for preparing the collagen molecule@graphene oxide composite according to claim 1, characterized in that: In step 1), the enzymatic activity of the alkaline protease ranges from 200,000 to 500,000 u / g, the pH value is 9 to 11, and the applicable temperature is 50 to 60°C; the first amphoteric surfactant and the second amphoteric surfactant are one or a mixture of N-dodecyl-aminopropionic acid sodium, dodecyl imidazoline betaine, N-dodecyl-N,N-dimethyl-N-carboxymethyl betaine and N,N-2-methyl (methacryloyloxyethyl) aminopropanesulfonic acid inner salt, the active matter mass percentage is 30%, and the pH value is 6.0 to 8.

0.

7. The method for preparing the collagen molecule@graphene oxide composite according to claim 1, characterized in that: In step 1), the oxygen content of the graphene oxide is 26.85 at%, and the particle size is 50-350 nm.

8. The method for preparing the collagen molecule@graphene oxide composite according to claim 1, characterized in that: In step 1), the pentaerythritol solution is prepared by mixing deionized water and pentaerythritol; the mass ratio of the graphene oxide, deionized water, pentaerythritol and collagen molecular spherical aggregate dispersion is (50-60): (80-100): (1-1.5): (200-250); and the stirring time is 20-30 min.

9. A collagen molecule@graphene oxide composite, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the collagen molecule@graphene oxide composite obtained by the preparation method according to any one of claims 1 to 8 in the preparation of cement-based materials, characterized in that: 20 to 30 parts of collagen molecules@graphene oxide composites are added to every 100 parts of cement-based materials.